High-entropy alloy fiber material with core-shell structure as well as preparation method and application of high-entropy alloy fiber material
The electrolyte composition and deposition conditions are optimized through the constant potential electrodeposition method, and the uniform deposition of high-entropy alloys on the surface of conductive fibers is achieved, which solves the problem of uneven deposition of high-entropy alloys, and obtains high-entropy alloy fiber materials with excellent conductivity and mechanical stability, which broadens its application in the development of flexible electronic equipment and electrodes.
Patent Information
- Application Number
- CN202510152319.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-12
AI Technical Summary
The prior art is difficult to achieve uniform and stable deposition of high-entropy alloys on the surface of conductive fibers, which limits its wide application in aerospace, electronic devices and energy fields.
By adopting the constant potential electrodeposition method, high-entropy alloys are uniformly deposited on the surface of conductive fibers by optimizing the electrolyte composition and deposition conditions, and a high-entropy alloy fiber material with core-shell structure is prepared.
High-entropy alloy fiber materials with excellent conductivity and mechanical stability were obtained, which solved the problem of uneven deposition of high-entropy alloys and broadened its application prospects in flexible electronic equipment and electrode development.
Smart Images

Figure CN119615318A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy material preparation, and more particularly to a high entropy alloy fiber material with a core-shell structure and a preparation method and application thereof. Background Art
[0002] High entropy alloy (HEA) is a new type of material composed of five or more metal elements in a disordered arrangement. At present, high entropy alloys have rich nanostructures compared with traditional alloys due to their multi-component structure, and exhibit excellent mechanical, electrochemical and magnetic properties. They are widely used in aerospace, electronic devices and energy fields. However, the preparation of high entropy alloys usually requires complex high-temperature treatment processes, such as arc melting, laser cladding and other methods. These methods are energy-intensive and costly, and are difficult to adapt to the needs of large-scale and low-temperature preparation. Electrochemical deposition (hereinafter referred to as electroplating) is a low-cost, easy-to-scale, and low-temperature metal preparation method and application, which is very suitable for the synthesis of high entropy alloys.
[0003] Electroplating is divided into substrate and coating. The coating is reduced from the electrolyte to the surface of the substrate by the action of electric current, thereby achieving the performance enhancement of the substrate. Therefore, the substrate is required to have certain conductive properties. Conductive fiber refers to a fiber material with conductivity. These fibers have wide application potential in the fields of electrodes, composite materials and wearables, and are very suitable as electroplating substrates. However, the current research on fiber materials is mostly concentrated in the field of composite materials, and there is still a lot of room for research on electrodes and wearable electronic materials, especially the combination of high entropy alloys and conductive fibers has not been deeply explored. Therefore, it is very important to use conductive fibers as the substrate to realize the preparation of electroplated high entropy alloy fibers.
[0004] However, electroplating high entropy alloys still has technical difficulties, and it is necessary to achieve uniform and stable deposition of high entropy alloys on the surface of conductive fibers. Therefore, how to develop a core-shell structured high entropy alloy fiber material and its preparation method and application is an urgent problem to be solved by those skilled in the art. Summary of the invention
[0005] In view of this, the present invention provides a high entropy alloy fiber material with a core-shell structure and a preparation method and application thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a core-shell structured high entropy alloy fiber material comprises the following steps:
[0008] (1) dissolving a buffer in deionized water to obtain solution A, heating solution A, and then sequentially adding a complexing agent, an additional salt, a reducing agent, and a soluble metal salt, stirring and dissolving to obtain solution B, allowing solution B to stand at room temperature, adjusting the pH of solution B, and obtaining an electrolyte;
[0009] The reducing agent is one or both of sodium hypophosphite and ascorbic acid; the soluble metal salt is iron salt, cobalt salt, nickel salt, copper salt and zinc salt;
[0010] (2) The conductive fiber was ultrasonically cleaned with acetone, ethanol and deionized water in sequence, then rinsed with deionized water and dried;
[0011] (3) using a saturated calomel electrode as a reference electrode, the conductive fiber obtained in step (2) as a working electrode, and a carbon electrode rod as a counter electrode, the electrolyte obtained in step (1) is used to electro-deposit the conductive fiber using a constant potential electrodeposition method, wherein the deposition potential range of the electrodeposition is -1 V to -2 V, thereby obtaining a high entropy alloy fiber material with a core-shell structure;
[0012] In step (1), the buffer is one or more of boric acid, disodium hydrogen phosphate, phosphoric acid or acetic acid; the complexing agent is one or more of citric acid, sodium citrate or potassium pyrophosphate; the additional salt is one or more of potassium chloride, sodium chloride or sodium sulfate;
[0013] In step (1), in solution A, the concentration of the buffer is 0.001-1 mol / L, in solution B, the concentration of the complexing agent is 0.001-1 mol / L, the concentration of the additional salt is 0.001-1 mol / L, and the concentration of the reducing agent is 0.001-1 mol / L;
[0014] The iron salt is one or more of ferrous sulfate, ferrous chloride or ferrous nitrate; the cobalt salt is one or more of cobalt sulfate, cobalt chloride or cobalt nitrate; the nickel salt is one or more of nickel sulfate, nickel chloride or nickel nitrate; the copper salt is one or more of copper sulfate, copper chloride or copper nitrate; the zinc salt is one or more of zinc sulfate, zinc chloride or zinc nitrate;
[0015] In solution B, the concentration of the iron salt is 0.001~1 mol / L, the concentration of the cobalt salt is 0.001~1 mol / L, the concentration of the nickel salt is 0.001~1 mol / L, the concentration of the copper salt is 0.0001~0.1 mol / L, and the concentration of the zinc salt is 0.001~1 mol / L;
[0016] In step (1), solution A is heated to 40-100° C., solution B is allowed to stand at room temperature for 2-8 hours, and the pH of solution B is adjusted to 1-5;
[0017] In step (2), the ultrasonic treatment time of the conductive fiber is 0 to 100 min, the ultrasonic power is 85 W, the drying temperature is 50 to 80°C, and the drying time is 2 to 10 hours;
[0018] In step (3), the electrodeposition time is 1 to 100 min, and the electrodeposition temperature is 20 to 100°C.
[0019] Furthermore, in step (2), the conductive fiber substrate is carbon fiber, metal conductive fiber or polymer conductive fiber; the conductive fiber has a diameter of 5-10 μm, a fiber length of 0.1-5 cm, and a plane resistance of <5 mΩ cm 2 Choosing a suitable conductive fiber substrate can achieve uniform and stable deposition of high-entropy alloys. At the same time, based on the weaving properties of high-entropy alloy fibers, it is conducive to the development of high-entropy alloy fibers in the field of flexible electronic devices. Conductive fibers are excellent conductors and can ensure the stable deposition of high-entropy alloy particles during the electrodeposition process.
[0020] Furthermore, in step (2), the metal conductive fibers are metal titanium fibers, metal silver fibers, etc., and the polymer conductive fibers are conductive polypyrrole fibers and conductive PEDOT fibers.
[0021] Furthermore, an acid solution and an alkali solution are used to adjust the pH of solution B, wherein the acid solution is a 1 mol / L H2SO4 solution, and the alkali solution is a 1 mol / L NaOH solution. By mixing the acid solution and the alkali solution, the pH of the electrolyte is stabilized within a predetermined range of 1 to 5, which can ensure the stability of the electroplating process and obtain uniform core-shell structure high entropy alloy fibers.
[0022] The present invention also provides a high entropy alloy fiber material with a core-shell structure prepared by the above method.
[0023] Furthermore, the fiber diameter of the high entropy alloy fiber material is 5-10 μm, the fiber length is 0.1-5 cm, the surface particle size is 100-1000 nm, the shell structure thickness is 100-1000 nm, the average contact impedance of the high entropy alloy fiber material at a frequency of 100 Hz is 33.30±1.03 kΩ, and the average solution impedance is 22.42±2.34 Ω. The physical morphology and surface microstructure of the core-shell structured high entropy alloy fiber are defined, and it is emphasized that the obtained high entropy alloy particles are nanosized.
[0024] Furthermore, the mass percentages of iron, cobalt, nickel, copper, and zinc in the core-shell high entropy alloy fiber material are 1% to 50%, respectively. Controlling the content of elements can ensure the element uniformity of the high entropy alloy fiber and prevent the excessive content of a single element from affecting the deposition process, particle size, etc. of the fiber material.
[0025] The present invention also provides an application of the high entropy alloy fiber material with the core-shell structure in the development of flexible electronic devices and electrodes.
[0026] Beneficial effects of the present invention:
[0027] The method of the present invention achieves uniform deposition of high entropy alloy by optimizing the electrolyte composition, thereby obtaining a high entropy alloy fiber material with excellent electrical conductivity and mechanical stability.
[0028] The present invention can accurately control the metal ion reduction, solubility and deposition rate in the electroplating process by optimizing the concentration of each component in solution B, thereby improving the uniformity and stability of the high entropy alloy deposition process on the conductive fiber surface.
[0029] The present invention introduces metal elements by adding metal salts to provide more choices for the metal source of high entropy alloys, can accurately control the electroplating process of high entropy alloys, and improve the uniformity of alloys. The metal elements are introduced by adding metal salts, which broadens the sources of metal elements and enriches the selection of high entropy alloys. The content of various elements in the electroplating process of high entropy alloys can be accurately controlled to improve the conductivity of the alloy. The static B solution can stabilize the electrolyte system, allowing the conductive fiber to remain stable during the deposition process.
[0030] The purpose of heating solution A in the present invention is to provide an external temperature source for the electrolyte system, increase the solubility of the system, and be conducive to dissolving the complexing agent, additional salt, reducing agent and soluble metal salt added subsequently, and provide a stable solution environment for the electrolyte. Standing solution B can stabilize the electrolyte system, allowing the conductive fiber to remain stable during the deposition process. Ultrasound can clean the surface of the conductive fiber, remove impurities generated on the surface of the fiber during the production process, increase the contact points between the electrolyte and the conductive fiber during the electroplating process, and promote the uniform and stable electroplating process. The method of the present invention achieves uniform deposition of high entropy alloys by optimizing the deposition time, and obtains high entropy alloy fiber materials with excellent conductivity and mechanical stability. Obtaining a uniform high entropy alloy allows nano high entropy alloy particles to wrap the conductive fiber, improve the conductivity of the fiber, and add a layer of microstructure to the fiber surface, thereby increasing the number of active sites.
[0031] The present invention selects the deposition potential range of -1 V to -2 V for electrodeposition, which is more conducive to the deposition of multiple metal elements, and avoids the potential being too positive to cause the metal ions to be unable to be reduced, and avoids the potential being too negative to cause hydrogen to be precipitated. An overly negative potential can cause the electrolysis of water to produce hydrogen, which not only affects the electrodeposition process, but also may cause uneven deposition or bubble defects.
[0032] Compared with the traditional binary alloy system such as the traditional iron-nickel alloy, from the preparation process: the preparation of the high entropy alloy of the present invention needs to solve the problem of uniform mixing of multiple elements, while avoiding the formation of intermetallic compounds and achieving uniform distribution of five elements, and the process method is relatively difficult. The production of ordinary binary alloys relies on traditional alloy technology, the system is mature and the composition is simple.
[0033] The carbon-based high entropy alloy fiber prepared by the method of the present invention has a nanoscale microstructure, and realizes a close combination of high entropy alloy and conductive fiber. The present invention uses acetone, ethanol and deionized water to clean the electrolyte residue on the surface of the material after electroplating, which is beneficial to the subsequent drying of the material. The temperature of electrodeposition is lower than that of other deposition methods. Traditional metal methods such as sputtering deposition of HEA are obtained by high-temperature sintering. The temperature of electrodeposition is 20~100℃, and uniform deposition of high entropy alloy is achieved under low temperature conditions, and a high entropy alloy fiber material with excellent conductivity and mechanical stability is obtained. The preparation process of the present invention is simple and low in cost, and the obtained material has broad application prospects in the fields of electrocatalysis, energy storage and structural composite materials.
[0034] The carbon-based high entropy alloy fiber material of the present invention has a nanoscale microstructure, and achieves close integration of the high entropy alloy and the conductive fiber, thereby providing a high entropy alloy fiber material with excellent conductivity and mechanical stability.
[0035] The core-shell structured high entropy alloy fiber material improves the conductivity of the raw materials and provides a larger specific surface area and more active sites with the help of nano-scale particles, making it have stronger application potential in the development of flexible electronic devices and electrodes, especially in the field of flexible electronic devices and electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is the SEM image of the core-shell structured high entropy alloy fiber material prepared in Example 1.
[0037] Figure 2 This is the EDS image of the core-shell structured high entropy alloy fiber material prepared in Example 1.
[0038] Figure 3 The contact impedance comparison between the core-shell high entropy alloy fiber material prepared in Example 1 and the commercial conductive material.
[0039] Figure 4 The solution impedance comparison between the core-shell high entropy alloy fiber material prepared in Example 1 and the commercial conductive material.
[0040] Figure 5 The element content ratios of the core-shell high entropy alloy fiber materials prepared in Examples 1 to 5.
[0041] Figure 6 In the figure, Figure a is the cyclic voltammetry test of the working electrode in the electrolyte, Figure b is the cyclic voltammetry test of the working electrode in a single metal element solution, Figure c is the deposition curve at different deposition potentials, and Figure d is the impedance performance of the electrode obtained at different deposition potentials. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] A method for preparing a high entropy alloy fiber material with a core-shell structure comprises the following steps:
[0045] (1) Boric acid was dissolved in deionized water to obtain solution A. The concentration of boric acid in solution A was 0.5 mol / L. Solution A was heated to 40°C, and then citric acid, sodium citrate, potassium chloride, sodium hypophosphite, ferrous sulfate, cobalt sulfate, nickel chloride, cupric chloride and zinc nitrate were added in sequence under heating conditions. After stirring and dissolving, solution B was obtained. The concentration of citric acid in solution B was 0.5 mol / L, the concentration of sodium citrate was 0.1 mol / L, the concentration of potassium chloride was 0.05 mol / L, the concentration of sodium hypophosphite was 0.01 mol / L, the concentration of ferrous sulfate was 0.05 mol / L, the concentration of cobalt sulfate was 0.01 mol / L, the concentration of nickel chloride was 0.01 mol / L, the concentration of cupric chloride was 0.0001 mol / L and the concentration of zinc nitrate was 0.01 mol / L. Solution B was allowed to stand at room temperature for 2 hours, and then a concentration of 1 mol / L H2SO4 solution to adjust the pH of solution B to 2 to obtain an electrolyte;
[0046] (2) The fiber diameter is 8 μm, the fiber length is 2 cm, and the plane resistance is less than 5 mΩ cm. 2The carbon fiber surface was ultrasonically treated with acetone, ethanol and deionized water for 100 min at an ultrasonic power of 85 W, then rinsed with deionized water and ethanol, and dried at 80 °C for 2 h.
[0047] (3) The electrolyte obtained in step (1) was used to electroplate the carbon fiber by constant potential electrodeposition, with a saturated calomel electrode as the reference electrode, the carbon fiber obtained in step (2) as the working electrode, the carbon electrode rod as the counter electrode, the deposition potential was -1.25 V, the electrodeposition temperature was 20 ° C, the electrodeposition time was 10 min, and a core-shell structured high entropy alloy fiber material was obtained. The obtained core-shell structured high entropy alloy fiber material has a fiber diameter of 8 μm, a fiber length of 2 cm, a surface particle size of 300-600 nm, and a shell structure thickness of about 100-300 nm.
[0048] like Figure 1 , is a SEM image of the core-shell structured high entropy alloy fiber material prepared in this embodiment. Among them, the surface particles are the shell of the core-shell structure, and the carbon fiber is the core of the core-shell structure. The SEM image shows that a stable synthesis of the high entropy alloy is formed and the distribution is uniform.
[0049] like Figure 2 , is the EDS image of the core-shell high entropy alloy fiber material prepared in this embodiment. From the EDS image, it can be seen that the five metal elements of iron, cobalt, nickel, copper and zinc are successfully deposited in the same area and are evenly distributed.
[0050] like Figure 3 , which is a comparison of the contact impedance between the core-shell structured high entropy alloy fiber material prepared in this embodiment and the commercial material, indicating that the core-shell structured high entropy alloy fiber material has a lower resistance when in contact with the skin. Among them, at a frequency of 100 Hz, the average contact impedance of the commercial material is 171.40 kΩ, the average contact impedance of the planar HEA is 43.32 kΩ, and the average contact impedance of the fiber HEA is 33.30 kΩ.
[0051] The commercial material is a commercial two-dimensional conductive material, the planar HEA is a HEA material obtained by electrodeposition on a two-dimensional plane, and the fiber HEA is the high entropy alloy fiber material with a core-shell structure in Example 1.
[0052] like Figure 4, which is a comparison of the solution impedance of the core-shell structured high entropy alloy fiber material prepared in this embodiment and the commercial conductive material, indicating that the core-shell structured high entropy alloy fiber material has a smaller resistance in the electrolyte environment of phosphate buffer (PBS). Among them, at a frequency of 100 Hz, the average solution impedance of the commercial material is 234.03 kΩ, the average solution impedance of the planar HEA is 123.44 kΩ, and the average solution impedance of the fiber HEA is 22.42 kΩ.
[0053] Example 2
[0054] A method for preparing a high entropy alloy fiber material with a core-shell structure comprises the following steps:
[0055] (1) Acetic acid and disodium hydrogen phosphate were dissolved in deionized water to obtain solution A. In solution A, the concentration of acetic acid was 0.001 mol / L, and the concentration of disodium hydrogen phosphate was 0.001 mol / L. Solution A was heated to 100°C, and then citric acid, sodium citrate, sodium chloride, ascorbic acid, ferrous chloride, cobalt nitrate, nickel sulfate, copper sulfate and zinc sulfate were added in sequence under heating conditions. After stirring and dissolving, solution B was obtained. In solution B, the concentration of citric acid was 0.05 mol / L, the concentration of sodium citrate was 0.001 mol / L, the concentration of sodium chloride was 0.05 mol / L, the concentration of ascorbic acid was 0.001 mol / L, the concentration of ferrous chloride was 1 mol / L, the concentration of cobalt nitrate was 0.05 mol / L, the concentration of nickel sulfate was 0.01 mol / L, the concentration of copper sulfate was 0.0001 mol / L, the concentration of zinc sulfate was 0.001 mol / L, leaving solution B at room temperature for 8 hours, and then adjusting the pH of solution B to 5 with a 1 mol / L NaOH solution to obtain an electrolyte;
[0056] (2) The fiber diameter is 5 μm, the fiber length is 0.1 cm, and the plane resistance is less than 5 mΩ cm. 2 The surface of polypyrrole conductive fiber was ultrasonically treated with deionized water for 0 min at an ultrasonic power of 85 W, then rinsed with deionized water and ethanol, and dried at 50 °C for 10 h;
[0057] (3) The electrolyte obtained in step (1) was used to electroplate the polypyrrole conductive fiber by constant potential electrodeposition, with a saturated calomel electrode as a reference electrode, the polypyrrole conductive fiber obtained in step (2) as a working electrode, and a carbon electrode rod as a counter electrode. The deposition potential was -1.75 V, the electrodeposition temperature was 40°C, and the electrodeposition time was 100 min to obtain a core-shell structured high entropy alloy fiber material. The obtained core-shell structured high entropy alloy fiber material had a fiber diameter of 5 μm, a fiber length of 0.1 cm, a surface particle size of 200-400 nm, and a shell structure thickness of 600-1000 nm.
[0058] Example 3
[0059] A method for preparing a high entropy alloy fiber material with a core-shell structure comprises the following steps:
[0060] (1) Phosphoric acid is dissolved in deionized water to obtain solution A, wherein the concentration of phosphoric acid in solution A is 0.001 mol / L. Solution A is heated to 40°C, and then citric acid, sodium citrate, sodium sulfate, sodium hypophosphite, ferrous chloride, cobalt chloride, nickel chloride, copper chloride and zinc chloride are added in sequence under heating conditions, and stirred to dissolve to obtain solution B, wherein the concentration of citric acid in solution B is 1 mol / L, the concentration of sodium citrate is 1 mol / L, the concentration of sodium sulfate is 0.001 mol / L, the concentration of sodium hypophosphite is 1 mol / L, the concentration of ferrous chloride is 0.001 mol / L, the concentration of cobalt chloride is 0.035 mol / L, the concentration of nickel nitrate is 1 mol / L, the concentration of copper nitrate is 0.001 mol / L, and the concentration of zinc chloride is 1 mol / L. Solution B is allowed to stand at room temperature for 2 hours, and then the pH of solution B is adjusted to 3 with a 1 mol / L H2SO4 solution to obtain an electrolyte;
[0061] (2) The fiber diameter is 10 μm, the fiber length is 1 cm, and the plane resistance is less than 5 mΩ cm. 2 The surface of the conductive PEDOT fiber was ultrasonically treated with deionized water for 20 min at an ultrasonic power of 85 W, then rinsed with deionized water and ethanol, and dried at 80 °C for 4 h.
[0062] (3) Using the electrolyte obtained in step (1), the conductive PEDOT fiber is electroplated by constant potential electrodeposition, with a saturated calomel electrode as the reference electrode, the conductive PEDOT fiber obtained in step (2) as the working electrode, and the carbon electrode rod as the counter electrode. The deposition potential is -2 V, the electrodeposition temperature is 60°C, and the electrodeposition time is 1 min to obtain a core-shell structured high entropy alloy fiber material. The obtained core-shell structured high entropy alloy fiber material has a fiber diameter of 10 μm, a fiber length of 1 cm, a surface particle size of about 400-600 nm, and a shell structure thickness of 100-200 nm.
[0063] Example 4
[0064] A method for preparing a high entropy alloy fiber material with a core-shell structure comprises the following steps:
[0065] (1) Boric acid was dissolved in deionized water to obtain solution A. In solution A, the concentration of boric acid was 1 mol / L. Solution A was heated to 50°C, and then citric acid, sodium citrate, potassium pyrophosphate, sodium chloride, sodium hypophosphite, ferrous sulfate, cobalt sulfate, nickel nitrate, copper chloride and zinc chloride were added in sequence under heating conditions. After stirring and dissolving, solution B was obtained. In solution B, the concentration of citric acid was 0.5 mol / L, the concentration of sodium citrate was 1 mol / L, the concentration of potassium pyrophosphate was 0.001 mol / L, the concentration of sodium chloride was 1 mol / L, the concentration of sodium hypophosphite was 0.01 mol / L, the concentration of ferrous sulfate was 0.1 mol / L, the concentration of cobalt sulfate was 1 mol / L, the concentration of nickel nitrate was 0.05 mol / L, the concentration of copper sulfate was 0.001 mol / L and the concentration of zinc sulfate was 0.005 mol / L. Solution B was allowed to stand at room temperature for 8 hours, and then a concentration of 1 mol / L H2SO4 solution to adjust the pH of solution B to 1 to obtain an electrolyte;
[0066] (2) The fiber diameter is 6 μm, the fiber length is 1.5 cm, and the plane resistance is less than 5 mΩ cm. 2 The titanium fiber was ultrasonically treated with deionized water for 60 min at an ultrasonic power of 85 W, then rinsed with deionized water and ethanol, and dried at 60 °C for 6 h.
[0067] (3) Using the electrolyte obtained in step (1), the titanium fiber is electroplated by constant potential electrodeposition, with a saturated calomel electrode as the reference electrode, the titanium fiber obtained in step (2) as the working electrode, and the carbon electrode rod as the counter electrode. The deposition potential is -1 V, the electrodeposition temperature is 80°C, and the electrodeposition time is 20 min to obtain a core-shell structured high entropy alloy fiber material. The obtained core-shell structured high entropy alloy fiber material has a fiber diameter of 6 μm, a fiber length of 1.5 cm, a surface particle size of 600-1000 nm, and a shell structure thickness of 100-200 nm.
[0068] Example 5
[0069] A method for preparing a high entropy alloy fiber material with a core-shell structure comprises the following steps:
[0070] (1) Boric acid was dissolved in deionized water to obtain solution A. In solution A, the concentration of boric acid was 1 mol / L. Solution A was heated to 60°C, and then citric acid, sodium citrate, potassium chloride, sodium hypophosphite, ferrous sulfate, cobalt sulfate, nickel sulfate, copper sulfate and zinc sulfate were added in sequence under heating conditions. After stirring and dissolving, solution B was obtained. In solution B, the concentration of citric acid was 0.001 mol / L, the concentration of sodium citrate was 0.35 mol / L, the concentration of potassium chloride was 0.05 mol / L, the concentration of sodium hypophosphite was 0.005 mol / L, the concentration of ferrous sulfate was 1 mol / L, the concentration of cobalt chloride was 1 mol / L, the concentration of nickel sulfate was 0.05 mol / L, the concentration of copper sulfate was 0.1 mol / L and the concentration of zinc sulfate was 0.05 mol / L. Solution B was allowed to stand at room temperature for 5 hours, and then a concentration of 1 mol / L H2SO4 solution to adjust the pH of solution B to 1 to obtain an electrolyte;
[0071] (2) The fiber diameter is 8 μm, the fiber length is 5 cm, and the plane resistance is less than 5 mΩ cm. 2 The silver fiber surface was ultrasonically treated with deionized water for 45 min at an ultrasonic power of 85 W, then rinsed with deionized water and ethanol, and dried at 60 °C for 5 h.
[0072] (3) The electrolyte obtained in step (1) was used to electroplate the silver fiber by constant potential electrodeposition, with a saturated calomel electrode as the reference electrode, the silver fiber obtained in step (2) as the working electrode, and the carbon electrode rod as the counter electrode. The deposition potential was -1.5 V, the electrodeposition temperature was 100 ° C, and the electrodeposition time was 20 min to obtain a core-shell structured high entropy alloy fiber material. The obtained core-shell structured high entropy alloy fiber material has a fiber diameter of 8 μm, a fiber length of 5 cm, a surface particle size of 100-300 nm, and a shell structure thickness of 200-400 nm.
[0073] like Figure 5 , which is a data chart of element contents of the core-shell structured high entropy alloy fiber materials prepared in Examples 1 to 5. The deposition of the five metal elements can be seen from the contents of each element, indicating that the method can stably achieve the stable synthesis of the core-shell structured high entropy alloy fiber.
[0074] The present invention realizes uniform and stable deposition of high entropy alloy on the surface of conductive fiber, and further improves the electrical properties of conductive fiber while maintaining the characteristics of conductive fiber.
[0075] Selection of potential range for electrodeposition:
[0076] In the present invention, cyclic voltammetry was used to find that the electrodeposition interval was found from 0 V to -0.6 V ( Figure 6 a and b), so -1 V, which is negative to -0.6 V, was selected as the starting research position. However, during the electrodeposition process, although the deposition potential of -1 V can obtain high entropy alloy, there is an instantaneous change in current before electrodeposition. This is due to the electrode charging phenomenon caused by insufficient electrodeposition voltage. Although the preparation of high entropy alloy is achieved at -2 V, hydrogen is easily precipitated during the entire deposition process, affecting the stability of the high entropy alloy preparation process ( Figure 6 c), while -1.25 V is the most suitable deposition potential because the preparation process is stable, the resulting material has lower electrical impedance and better conductivity. Figure 6 d figure), the present invention has an entire deposition potential range centered at -1.25 V, and high entropy alloys can be prepared by selecting -1 V to -2 V.
[0077] Regarding the selection of -1 V: -1 V is selected to ensure that the potential is a negative value. For the multi-element deposition process, since the target element has a positive standard potential, choosing a negative potential is more conducive to the deposition of multiple metal elements and avoids the potential being too positive during the experiment, which may lead to the inability to reduce metal ions.
[0078] Regarding the choice of -2 V: -2 V is chosen to avoid hydrogen evolution due to overly negative potential. Overly negative potential will cause water electrolysis and produce hydrogen, which will not only affect the electrodeposition process, but may also cause uneven deposition or bubble defects, but high entropy alloys can be obtained.
[0079] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a core-shell structured high entropy alloy fiber material, characterized in that: The steps include: (1) dissolving a buffer in deionized water to obtain solution A, heating solution A, and then sequentially adding a complexing agent, an additional salt, a reducing agent, and a soluble metal salt, stirring and dissolving to obtain solution B, allowing solution B to stand at room temperature, adjusting the pH of solution B, and obtaining an electrolyte; The reducing agent is one or both of sodium hypophosphite and ascorbic acid; the soluble metal salt is iron salt, cobalt salt, nickel salt, copper salt and zinc salt; (2) The conductive fiber was ultrasonically cleaned with acetone, ethanol and deionized water in sequence, then rinsed with deionized water and dried; (3) using a saturated calomel electrode as a reference electrode, the conductive fiber obtained in step (2) as a working electrode, and a carbon electrode rod as a counter electrode, the electrolyte obtained in step (1) is used to electro-deposit the conductive fiber using a constant potential electrodeposition method, wherein the deposition potential range of the electrodeposition is -1 V to -2 V, to obtain a high entropy alloy fiber material with a core-shell structure; In step (1), the buffer is one or more of boric acid, disodium hydrogen phosphate, phosphoric acid or acetic acid; the complexing agent is one or more of citric acid, sodium citrate or potassium pyrophosphate; the additional salt is one or more of potassium chloride, sodium chloride or sodium sulfate; In step (1), in solution A, the concentration of the buffer is 0.001-1 mol / L, in solution B, the concentration of the complexing agent is 0.001-1 mol / L, the concentration of the additional salt is 0.001-1 mol / L, and the concentration of the reducing agent is 0.001-1 mol / L; The iron salt is one or more of ferrous sulfate, ferrous chloride or ferrous nitrate; the cobalt salt is one or more of cobalt sulfate, cobalt chloride or cobalt nitrate; the nickel salt is one or more of nickel sulfate, nickel chloride or nickel nitrate; the copper salt is one or more of copper sulfate, copper chloride or copper nitrate; the zinc salt is one or more of zinc sulfate, zinc chloride or zinc nitrate; In solution B, the concentration of the iron salt is 0.001 to 1 mol / L, the concentration of the cobalt salt is 0.001 to 1 mol / L, the concentration of the nickel salt is 0.001 to 1 mol / L, the concentration of the copper salt is 0.0001 to 0.1 mol / L, and the concentration of the zinc salt is 0.001 to 1 mol / L; In step (1), solution A is heated to 40-100° C., solution B is allowed to stand at room temperature for 2-8 hours, and the pH of solution B is adjusted to 1-5; In step (2), the ultrasonic treatment time of the conductive fiber is 0 to 100 min, the ultrasonic power is 85 W, the drying temperature is 50 to 80°C, and the drying time is 2 to 10 hours; In step (3), the electrodeposition time is 1 to 100 min, and the electrodeposition temperature is 20 to 100°C.
2. The method for preparing a core-shell high entropy alloy fiber material according to claim 1, characterized in that: In step (2), the conductive fiber is carbon fiber, metal conductive fiber or polymer conductive fiber; the conductive fiber diameter is 5-10 μm, the conductive fiber length is 0.1-5 cm, and the plane resistance is less than 5 mΩ cm 2 .
3. A high entropy alloy fiber material with a core-shell structure prepared by the method according to any one of claims 1 to 2.
4. The high entropy alloy fiber material with a core-shell structure according to claim 3, characterized in that: The fiber diameter of the high entropy alloy fiber material is 5-10 μm, the fiber length is 0.1-5 cm, the surface particle size is 100-1000 nm, the shell structure thickness is 100-1000 nm, the average contact impedance of the high entropy alloy fiber material at a frequency of 100 Hz is 33.30±1.03 kΩ, and the average solution impedance is 22.42±2.34Ω.
5. Application of the high entropy alloy fiber material with a core-shell structure as claimed in claim 3 or 4 in the development of flexible electronic devices and electrodes.
Citation Information
Patent Citations
Iron-cobalt-nickel-copper-based high-entropy alloy water electrolysis catalytic material and preparation method thereof
CN111185188A
Preparation method of carbon fiber fabric electroplating solution
CN113668020A
Preparation method of FeCoNiCuZn high-entropy alloy and FeCoNiCuZn high-entropy alloy
CN116970996A
Method for preparing high-entropy alloy coating catalyst by utilizing pulse electrodeposition
CN118028930A
Preparation method and application of high-entropy alloy and carbon fiber composite nanomaterial
CN118389966A
Cited By
Bipolar plate composite coating preparation method based on high-entropy alloy and conductive polymer
CN121204768A